2020
DOI: 10.1371/journal.pntd.0007534
|View full text |Cite
|
Sign up to set email alerts
|

Adding MASP1 to the lectin pathway—Leprosy association puzzle: Hints from gene polymorphisms and protein levels

Abstract: Background Deposition of complement factors on Mycobacterium leprae may enhance phagocytosis. Such deposition may occur through the lectin pathway of complement. Three proteins of the lectin pathway are produced from the gene MASP1: Mannan-binding lectin-associated serine protease 1 (MASP-1) and MASP-3 and mannan-binding lectin-associated protein of 44 kDa (MAp44). Despite their obvious importance, the roles played by these proteins have never been investigated in leprosy disease. Methodology We haplotyped fiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Polymorphisms of both MBL-associated serine protease-encoding genes were associated with HBV infection. We also confirmed the recently published association with leprosy disease and the MASP1*GC_CCG haplotype, obtained with the same group of patients (OR = 1.81 [95%CI = 1.25–2.64], P = 0.002) ( 29 ). Furthermore, we identified an opposite association with the MASP1*GC_CCA haplotype, with leprosy resistance (OR = 0.50 [95%CI = 0.28–0.89], P = 0.019).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Polymorphisms of both MBL-associated serine protease-encoding genes were associated with HBV infection. We also confirmed the recently published association with leprosy disease and the MASP1*GC_CCG haplotype, obtained with the same group of patients (OR = 1.81 [95%CI = 1.25–2.64], P = 0.002) ( 29 ). Furthermore, we identified an opposite association with the MASP1*GC_CCA haplotype, with leprosy resistance (OR = 0.50 [95%CI = 0.28–0.89], P = 0.019).…”
Section: Resultssupporting
confidence: 91%
“…Instead, it cleaves pro-factor D from the PRM-independent alternative pathway (AP) in “resting” blood (under non-inflammatory conditions) [reviewed by ( 62 )]. The MASP1*AC_CC haplotype associated with higher susceptibility to HBV infection presents a 3′UTR combination in exon 12 that possibly acts as a target for miRNAs, being also associated with higher MASP-3 and lower MASP-1 levels ( 29 ). Thus, the association of this MASP1 haplotype with HBV susceptibility may be explained by blockage/hindered LP activation, as well as excessive AP activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinical associations of MASP-1, MASP-3, and MAp44 other than 3MC have been reported. For example, Weinschutz Mendes et al (2020) found that polymorphisms influencing serum concentrations of MASP-3/MAp44 modulate susceptibility to leprosy [33]. Larsen et al (2019) showed that low MASP-1 concentrations were associated with clotting disorders in patients with septic shock [34].…”
Section: Biological Activities Of the Masp-1 Masp-3 And Map44mentioning
confidence: 99%
“…In fact, lower MASP-2, MASP-3 and MAp44 levels occur in leprosy and lepromatous disease, probably due to its consumption in the inflammatory response. On the other hand, MASP1 haplotypes associated with lower MASP-1 and higher MASP-3 levels at baseline were associated with leprosy resistance, probably by decreasing mycobacteria infection, which relies on successful complement-driven opsonization and phagocytosis ( Boldt et al ., 2013 ; Weinschutz Mendes et al ., 2020 ). Thus, the investigation of MASP levels in COVID-19 is also highly relevant, especially in the context of comorbidities.…”
Section: Introductionmentioning
confidence: 99%